O uso da Geometria do Táxi no ensino de Análise Combinatória - Caldato, Patrícia [UNESP] (2013)
This work presented a sequence of activities which aim at teaching of Combinatorial Analysis using the Taxicab Geometry, a geometry that is able of modeling the trajectories, of citizens and vehicles moving on blocks, along the axis of streets and avenues. These activities have been applied to a group of High School students, having as a teaching resource a game and using the Problem Solving methodology. The intention was to purpose lessons to flee that old routine of a traditional methodology where the resources are only involved as chalk, blackboard or textbook, trying to attract more students' attention and connect teaching of Mathematics to them life